1986
DOI: 10.1021/jf00071a015
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of cyclitols in carob pods (Ceratonia siliqua L.)

Abstract: In the food industry, carob powder is used as a cocoa substitute. It consists primarily of sugars (sucrose, glucose, fructose) in addition to tannins, fibers, etc. D-(+)-Pinitol (3-0-methyl-D-c/zzro-inositol), myoinositol, and D-(+)-c/zt'ro-inositol were isolated from a fermented water extract of carob powder. The concentration of pinitol ranged from 5 to 7.5% of the dry weight of the powder as determined by GC. myo-inositol and c/zzro-inositol were minor components with concentrations of 0.5 to 1% and 0.1%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…The concentration of d -pinitol is influenced by genetic and environmental factors; especially the mean d -pinitol content of wild carob cultivars is higher than mean d -pinitol content of cultivated ones [35]. The presence of d -pinitol is of high importance as it can be used as a marker of carob adulteration by cocoa [39]. In addition, carob bean can be considered as an excellent reservoir of d -pinitol and its isolation procedure has been patented [40].…”
Section: Functional Chemical Components Of Carob Fruitmentioning
confidence: 99%
“…The concentration of d -pinitol is influenced by genetic and environmental factors; especially the mean d -pinitol content of wild carob cultivars is higher than mean d -pinitol content of cultivated ones [35]. The presence of d -pinitol is of high importance as it can be used as a marker of carob adulteration by cocoa [39]. In addition, carob bean can be considered as an excellent reservoir of d -pinitol and its isolation procedure has been patented [40].…”
Section: Functional Chemical Components Of Carob Fruitmentioning
confidence: 99%
“…202 It is important to indicate here that in this review article we tried to focus our attention on major natural products found in Carob, despite the fact that some compounds that are found in trace amounts, might be of some interest. 203 But these compounds are found in other plants in higher amounts and were studied in that context.…”
Section: Discussionmentioning
confidence: 99%
“…This cyclitol has been described as the predominant polyalcohol of carob and has been proposed as a natural marker to detect adulterations in cocoa products [34]. Since no pinitol was found in coffee extracts, it might be also employed as a marker of coffee adulteration.…”
Section: Composition Of Coffee Substitutesmentioning
confidence: 99%